The intestinal microbiota modulates the visceral sensitivity involved in IBS induced by restraint combined with tail clustering - Deng, Na; Xie, Siqin; Liu, Qin; Peng, Huiyi; Fang, Leyao; Shen, Junxi; Lin, Xiaoyuan (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveTo compare three common stimuli that induce emotional stress to identify the optimal method for establishing an animal model that aligns with the clinical pathogenesis of irritable bowel syndrome (IBS) and to explore the gut microbiota mechanisms underlying IBS development.MethodsThirty-six SPF-grade female Kunming mice were randomly divided into four groups: the normal control (NC) group, the restraint stress (BM) group, the tail clamp stress (CTM) group, and the restraint combined with tail clamp stress (BCTM) group, with 9 mice in each group. The NC group was fed normally without any stimulation. The BM group was subjected to restraint stress. The CTM group received intermittent tail clamp stress. The BCTM group underwent both restraint stress and intermittent tail clamp stress. The stimulation time for each group was 1 hour, and the modeling duration was 7 days. General behavioral changes in the mice were observed. The fecal water content was measured and calculated. The pain threshold, gastric residue rate, small intestine propulsion rate, and serum levels of short-chain fatty acids (SCFAs), serotonin (5-HT), interleukin-10 (IL-10), and tumor necrosis factor-alpha (TNF-α) were assessed. Histopathological analysis of the small intestine and colon tissues was performed. 16S rRNA high-throughput sequencing was subsequently conducted. The effects of different stimuli on mouse symptoms, gastrointestinal motility, visceral hypersensitivity, inflammation levels, and the gut microbiota were analyzed, and correlation analysis was performed.ResultsCompared with the NC group, the BM, CTM, and BCTM groups of mice presented varying degrees of emotional hyperreactivity, accompanied by significantly reduced food intake and fecal water content and markedly elevated levels of inflammation, all of which are indicative of IBS symptoms. Among them, the BCTM group presented the most pronounced emotional hyperreactivity and irritability. The mice in the BCTM group had significantly higher gastric residue rates and 5-HT levels, with a marked reduction in pain tolerance. The gut microbiota of the mice in the BM, CTM, and BCTM groups all exhibited dysbiosis, with changes in the diversity, structural composition, and function of the microbial community. Specific bacterial taxa were enriched in each stress group, and their corresponding KEGG pathways were also significantly altered. Correlation analysis revealed that SCFAs were significantly positively correlated with the small intestine propulsion rate, whereas 5-HT was positively correlated with the gastric residue rate and negatively correlated with the pain threshold. SCFAs were positively correlated with IL-10 and TNF-α, and 5-HT was significantly positively correlated with IL-10 and TNF-α. In the BCTM group, the characteristic bacteria Acinetobacter and Akkermansia were significantly correlated with SCFAs and 5-HT.Conclusion1. The restraint combined with the tail clamp stress method is superior among the three stress protocols and successfully induces the IBS mouse model. 2. Acinetobacter and Akkermansia may contribute to the development of IBS induced by restraint combined with tail clamp stress through the regulation of SCFAs and 5-HT.